Characteristics of Pin Profile Variations in Friction Stir Welding (FSW) Joints of High Density Polyethylene (HDPE) And Polypropylene (PP) on Mechanical Properties - Ramadhani, Risky; Darsono, Febri Budi; Bahatmaka, Aldias; Kriswanto, Kriswanto; Prasdika, Tegar Oki; Azara, Salsa Bila (Universitas Sultan Ageng Tirtayasa, 2025)
In the Friction Stir Welding (FSW) process, the pin profile is one of the key factors in determining the quality of the joint because it directly affects the material flow in the joint area and the heat distribution generated during welding. Therefore, this study aims to determine the characteristics of pin profile variations in high-density polyethylene (HDPE)-polypropylene (PP) joints. Three types of pin profiles were used: threaded cylindrical pins, triangular pins, and grooved tapered cylindrical pins. The feed rate was 15 mm/min, the feed depth was 3.96 mm, and the rotating speed was 930 rpm. Hardness, tensile, bending, and macro-photo tests were conducted to determine the mechanical properties of the joints. The results showed that the grooved tapered cylindrical profile pin obtained the highest average value for hardness at 62.7 SHD, and tensile strength at 11.1 MPa. The lowest average values were obtained for the threaded cylindrical profile pins at 61.6 SHD, and 4.2 MPa. Flexural strength with the highest average value of 13.9 MPa was obtained for the triangular profile pin, while the lowest average value of 4.9 MPa was obtained for the threaded cylindrical profile pin. The strength test results, and macro photographs show that the shape and design of the profile pins play an important role in heat generation through friction as well as the control of material flow dynamics, which directly determines the structural integrity and mechanical properties of the joint.